2001
DOI: 10.1086/318071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Anal Human Papillomavirus Infection in Human Immunodeficiency Virus (HIV)–Positive and High‐Risk HIV‐Negative Women

Abstract: Little is known about the epidemiology of anal human papillomavirus (HPV) infection in women. We studied 251 human immunodeficiency virus (HIV)-positive and 68 HIV-negative women for the presence of anal HPV by use of polymerase chain reaction (PCR) and hybrid capture. Medical and behavioral risk factors were evaluated; 76% of HIV-positive and 42% of HIV-negative women were found to have anal HPV DNA via analysis by PCR (relative risk [RR], 1.8; 95% confidence interval [CI], 1.3-2.5). Among 200 women for whom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
214
6
21

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(269 citation statements)
references
References 34 publications
28
214
6
21
Order By: Relevance
“…Low CD4+ T lymphocyte cell counts significantly increased the likelihood of having cervical SIL, with most of the lesions seen at CD4+ T Lymphocyte cell counts below 200cells/µL. This is in agreement with most reports on rate of cervical SIL and HIV infection (Wright et al, 1994;Massad, 1999), possibly due to reactivation and persistent infection with the higher risky HPV such as type 16 and 18 (Wright et al, 1994;Palefsky et al, 2001). The significant statistical difference between the degree of immunosupression (by CD4+ T-lymphocyte cell counts) and the degree of cervical SIL shows that the more the immunity is suppressed the higher the likelihood of having high grade cervical SIL.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Low CD4+ T lymphocyte cell counts significantly increased the likelihood of having cervical SIL, with most of the lesions seen at CD4+ T Lymphocyte cell counts below 200cells/µL. This is in agreement with most reports on rate of cervical SIL and HIV infection (Wright et al, 1994;Massad, 1999), possibly due to reactivation and persistent infection with the higher risky HPV such as type 16 and 18 (Wright et al, 1994;Palefsky et al, 2001). The significant statistical difference between the degree of immunosupression (by CD4+ T-lymphocyte cell counts) and the degree of cervical SIL shows that the more the immunity is suppressed the higher the likelihood of having high grade cervical SIL.…”
Section: Discussionsupporting
confidence: 86%
“…This group was also seen to have a higher rate of HIV infection compared to married/cohabiting women). Multiple partners and HIV infection are factors highly associated with higher rates HPV infections, persistence and progression to SIL (Palefsky et al, 2001;Massad, 1999). A similar trend, however insignificant was seen with single/widowed developing HGL compared to married women in a West African study (La Ruche et al, 1998).…”
Section: Discussionmentioning
confidence: 73%
“…However, our data appear to be consistent with many other populations of HIV-infected women and men, where a significant increase in anogenital HPV prevalence and multiple infections has been reported. 18 The fact that genotypes other than HPV-16 are seen at relatively high frequency in this population may also be due to HIV, as others have reported that these HPV types, but not HPV-16, are more likely to increase in prevalence following HIV seroconversion (R. Burk, personal communication). Together, these data are important to the design of rational vaccine strategies in the sub-Saharan African nations.…”
Section: Dear Sirmentioning
confidence: 81%
“…9 In fact, it has been reported that approximately 93% of HIV-positive men and 76% of HIV-positive women have anal HPV infection. 10,11 Overexpression of p16 has been proposed as a useful surrogate biomarker in the identification of squamous lesions harboring HPV DNA. A previous study has demonstrated that the degree of p16 overexpression correlates with the degree of dysplasia in the uterine cervix.…”
mentioning
confidence: 99%